Neutrophil gelatinase-associated lipocalin (NGAL) predicts the occurrence of malaria-induced acute kidney injury. (December 2016) - Wolfswinkel, Marlies; Koopmans, Liese; Hesselink, Dennis; Hoorn, Ewout; Koelewijn, Rob; Hellemond, Jaap; Genderen, Perry
Abstract Background Acute kidney injury (AKI) is a frequently encountered complication of importedPlasmodium falciparum infection. Markers of structural kidney damage have been found to detect AKI earlier than serum creatinine-based prediction models but have not yet been evaluated in imported malaria. This pilot study aims to explore the predictive performance of neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) for AKI in travellers with importedP. falciparum infection. Methods Thirty-nine patients with imported falciparum malaria from the Rotterdam Malaria Cohort with available serum and urine samples at presentation were included. Ten of these patients met the criteria for severe malaria. The predictive performance of NGAL and KIM-1 as markers for AKI was compared with that of serum creatinine. Results Six of the 39 patients (15 %) developed AKI. Serum and urine NGAL and urine KIM-1 were all found to have large areas under the receiver operating characteristics curves (AUROC) for predicting AKI. Urine NGAL was found to have an excellent performance with positive predictive value (PPV) of 1.00 (95 % CI 0.54–1.00), a negative predictive value (NPV) of 1.00 (95 % CI 0.89–1.00) and an AUROC of 1.00 (95 % CI 1.00–1.00). Conclusion A good diagnostic performance of NGAL and KIM-1 for AKI was found. Particularly, urine NGAL was found to have an excellent predictive performance. Larger studies are needed to demonstrate whether these biomarkers are superior to serum creatinine as predictors for AKI inP. falciparum malaria.